Sustainability Finance Involves and Green Investment: A Literature Review Based on the Prisma Method - Nelson Simamora; Irma Setyawati; Andini Nurwulandari (International Journal of Economics and Management Research, 2024)
This study is a systematic literature review (SLR) that explores the factors influencing the development of sustainable finance and green finance. The study uses the SLR approach and follows the Prisma framework, identifying, evaluating, and synthesizing 19 relevant articles from the Scopus database published between 2020 and 2023. The articles investigate topics such as determinants of clean energy investment, the crucial role of green bonds, women's political empowerment, sustainability reporting, and their impact on financial performance, resource efficiency, and sustainable economic growth. Eleven of the reviewed articles employed quantitative methods such as regression, panel data analysis, and econometric modeling, while eight articles used qualitative methods such as case studies and systematic literature reviews. The results indicate a strong interest in examining the relationship between sustainable finance, green investments, and their impact on economic, environmental, and social aspects across different countries and industry sectors. This meta-analysis provides valuable insights and can serve as a basis for further efforts in promoting sustainable finance practices worldwide.